2018
DOI: 10.1186/s13071-018-2877-6
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal relationships between human and canine visceral leishmaniases in Belo Horizonte, Minas Gerais, 2006–2013

Abstract: BackgroundVisceral leishmaniasis is a serious public health problem in Brazil, and control of this disease constitutes a major challenge. The purpose of this study was to assess the existing spatial and temporal relationships between cases of canine visceral leishmaniasis (CanL) and human visceral leishmaniasis (HVL) recorded in Belo Horizonte, State of Minas Gerais, from 2006 to 2013.MethodsData provided by the Belo Horizonte Health Services regarding the disease control routine were analyzed in order to perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 22 publications
0
20
0
3
Order By: Relevance
“…In previous studies, we also used 6 hours to reflect the basic rhythm changes of clock genes . There are also studies that have detected gene rhythm changes once every 4 hours, and the addition of time points can more accurately reflect rhythmic changes. Therefore, we selected the 4‐hour interval to reflect rhythmic in the expression of clock genes.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we also used 6 hours to reflect the basic rhythm changes of clock genes . There are also studies that have detected gene rhythm changes once every 4 hours, and the addition of time points can more accurately reflect rhythmic changes. Therefore, we selected the 4‐hour interval to reflect rhythmic in the expression of clock genes.…”
Section: Discussionmentioning
confidence: 99%
“…In Cuiabá (ALMEIDA et al, 2012) and Várzea Grande (FUJIMORI et al, 2016) cities, studies in endemic neighbourhoods showed a higher prevalence than those found. This variation in prevalence may be due to differences in the local ecosystem that interfere with the development of the vector, socioeconomic differences or the techniques employed in each study (BRUHN et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A leishmaniose canina visceral (LCV) é uma doença zoonótica causada MG (BRUHN et al, 2018a). A correlação entre a LT e LV não foi considerada significativa (p = 0,3587; r = 0,2552) assim como a correlação entre LT e LCV (p = 0,6087; r = -0,11) por bairros, no mesmo período, em Ipatinga (Figura 27) (SARAIVA et al, 2011BELO et al, 2013b;BRUHN et al, 2018a;ABRANTES et al, 2018). Outros fatores que determinam as variações da distribuição geográfica da LCV foram relacionados às diferenças no ecossistema local, prioritariamente condições para a reprodução do vetor (FRANCO et al, 2011;ARAÚJO et al, 2013).…”
Section: Leishmaniose Canina Visceral (Lcv)unclassified
“…A opção de tratamento cabe exclusivamente ao proprietário do cão. O dono do animal tem obrigatoriedade de dar seguimento ao protocolo de tratamento com uso da miltefosina e reavaliação clínica e laboratorial sistemática, e uso de repelente para prevenir a picada do flebotomíneo (BRASIL, 2016b).3.3.1 Controle da LCVPublicação realizada na cidade de Natal, capital do Rio Grande do Norte, mostrou que as cadelas eram reservatório importante na cadeia de transmissão da LV, pela maior propensão à parasitemia relacionada ao menor nível de albumina presente no quadro de desnutrição desencadeada por múltiplas estratégia de controle da LV(BRUHN et al, 2018a).O uso de piretroides e a pulverização residual de casas e abrigos de animais são consideradas estratégias de controle eficazes contra flebotomíneos em ambientes peridomiciliares. A dificuldade encontrada na aplicação desses inseticidas refere-se ao seu uso em locais ao ar livre.…”
unclassified
See 1 more Smart Citation